Inhotim Institute: the experience of a museum complex and its relations with contemporary art, the environment and human development (PhD) (Cadernos de Sociomuseologia, 2020)
It is a study about the Inhotim Institute, open-air contemporary art museum and Botanical Garden located in Brumadinho, Minas Gerais, created from the private collection of Bernardo Paz, that is currently configured as an OSCIP – Civil Society Organization of Public Interest. The study proposes to detail the institution creation and trajectory in its axes of action – art, botany and environment, education, social inclusion – based on its institutional dynamics, between 2002 and 2018. It analyzes the process of musealization that puts in dialogue art and nature, and the paths designed over the territory, as well as its interlocution with surroundings, creating perspectives of human development. It addresses the experience of Inhotim in interaction with historical antecedents of contemporary art and New Museology, positioning it as a contemporary museological complex built in the interrelations between several fields of knowledge and the Integral Heritage. In it, meets together: the contradictions of contemporary times, environmental concerns, attention to the local development, the expansion of collections, disputes over resources and the search for the aesthetic experience of the beautiful through the art-landscape axis. The study concludes on the cross-linked potential of establishing links with the Sociomuseology, share strategies and create management processes aimed at fulfilling the social role of the museums, possible in any scenario, museological and many others, thus engaged. Keywords: Inhotim Institute; Contemporary art; Botanical garden; Contemporary museological complex; Sociomuseology.